2012
DOI: 10.1007/s10295-012-1130-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydroxypropyl-β-cyclodextrin on phytosterol biotransformation by different strains of Mycobacterium neoaurum

Abstract: Cyclodextrins (CDs) can improve productivity in the biotransformation of steroids by increasing conversion rate, conversion ratio, or substrate concentration. However, little is known of the proportion of products formed by multi-catabolic enzymes, e.g., via sterol side chain cleavage. Using three strains with different androst-1,4-diene-3,17-dione (ADD) to androst-4-ene-3,17-dione (AD) ratios, Mycobacterium neoaurum TCCC 11028 (MNR), M. neoaurum TCCC 11028 M1 (MNR M1), and M. neoaurum TCCC 11028 M3 (MNR M3), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…One of the problems is the low solubility of sterols in aqueous systems that results in poor availability of substrate to whole‐cell biocatalysts; the other is the inhibition of the side‐chain degradation process caused by the product AD(D) . Generally, the problem of low solubility can be partially relieved by strategies of micronization of substrate to fine particles, surfactant facilitated emulsification, water‐miscible co‐solvents, cyclodextrins, or application of biphasic systems . Product inhibition may be solved by selection of strains tolerant to high concentrations of steroid product or in situ product removal (ISPR) that can also be carried out in biphasic systems …”
Section: Introductionmentioning
confidence: 99%
“…One of the problems is the low solubility of sterols in aqueous systems that results in poor availability of substrate to whole‐cell biocatalysts; the other is the inhibition of the side‐chain degradation process caused by the product AD(D) . Generally, the problem of low solubility can be partially relieved by strategies of micronization of substrate to fine particles, surfactant facilitated emulsification, water‐miscible co‐solvents, cyclodextrins, or application of biphasic systems . Product inhibition may be solved by selection of strains tolerant to high concentrations of steroid product or in situ product removal (ISPR) that can also be carried out in biphasic systems …”
Section: Introductionmentioning
confidence: 99%
“…; Shen et al . ). However, little emphasis has been placed on how to reduce the decomposition of products in the process of biotransformation of phytosterols.…”
Section: Introductionmentioning
confidence: 97%
“…Several Letters in Applied Microbiology 61, 63--68 © 2015 The Society for Applied Microbiology significant gene clusters involved in the transformation of sterols were also identified in recent years, leading to the modification of target genes to reduce the production of by-products (Song et al 2010;Yao et al 2014). Furthermore, two-phase systems and cyclodextrins have been used to increase the solubility of steroid substrates in the aqueous phase (Donova et al 2007;Shen et al 2012). However, little emphasis has been placed on how to reduce the decomposition of products in the process of biotransformation of phytosterols.…”
Section: Introductionmentioning
confidence: 99%
“…In Mycobacterium, the microbial catabolic pathway of phytosterols is so complex that metabolic engineering with a rational design is very difficult. Recently, studies of Mycobacterium strains have reported that the solubility of phytosterols can be increased by adding hydroxypropyl-β-cyclodextrin (HP-β-CD) (Shen et al, 2012). This approach has been used for improving steroid biotransformation in aqueous media in strain ZJUVN-08 of M. neoaurum (Zhang X.Y.…”
Section: Introductionmentioning
confidence: 99%